The effect of heterogeneous nucleation site availability on rock microstructure: a new perspective from EBSD investigation - Stefano Peres; Thomas A. Griffiths; Matteo Masotta; Fabio Colle; Alessio Pontesilli; Stefano Iannini Lelarge; Lucia Mancini; Rainer Abart (Contributions to Mineralogy and Petrology, 2026)
In this study, we investigate the effect of the availability of sites for heterogeneous nucleation on the microstructure of moderately to highly undercooled synthetic trachybasalts under anhydrous and hydrous (2 wt% H₂O) conditions. Experiments were performed at 400 MPa by cooling melts from 1300 °C to target temperatures of 1150 °C, 1100 °C, and 1050 °C, followed by isothermal holds of 5 or 30 min. In one experimental series, 0.5 wt% Cr₂O₃ was added to increase the liquidus temperature of spinel and promote heterogeneous nucleation of clinopyroxene on spinel. All Cr-doped anhydrous samples comprise a high number of small skeletal crystals of clinopyroxene and spinel. Electron backscatter diffraction maps (EBSD) reveal the presence of crystallographic orientation relationships (CORs) at the interfaces shared between clinopyroxene and spinel grains situated in their centers, indicating heterogeneous nucleation of clinopyroxene on spinel. On the contrary, the Cr-free anhydrous samples are characterized by fewer large dendritic clinopyroxene crystals, which grew without significant competition from their neighbors because of the low amount of pre-existing spinel grains acting as heterogeneous nucleation sites. Our findings confirm that the availability of heterogeneous nucleation sites and the timing and sequence of nucleation can play a dominant role in shaping microstructures, more than compositional variations and nominal undercooling. Early formed mineral phases may act as seeds for heterogeneous nucleation and can potentially induce fast crystallization of magmatic systems that experience thermal or constitutional undercooling and increase magma viscosity, influencing its stagnation or fragmentation, depending on the crystallinity of the system.

Long-term trends in heat wave gaps for the New York City metropolitan area - Anthony Lin; Brian A. Colle (Urban Climate, 2025)

Identifying crystal nucleation mechanisms in a synthetic trachybasalt: a multimodal approach - Stefano Peres; Thomas A. Griffiths; Fabio Colle; Stefano Iannini Lelarge; Matteo Masotta; Alessio Pontesilli; Lucia Mancini; Rainer Abart (Contributions to Mineralogy and Petrology, 2024)
To develop new criteria to distinguish different crystal nucleation mechanisms in silicate melts, we performed crystallization experiments using a synthetic hydrous (2 wt% H 2 O) trachybasalt and combined three-dimensional information from synchrotron X-ray computed microtomography with two-dimensional mapping of crystallographic orientation relationships (CORs) using electron backscatter diffraction. Crystallization experiments were performed at 400 MPa by cooling the melt from 1300 °C to resting temperatures of 1150 and 1100 °C and maintaining isothermal conditions for 30 min and 8 h. Three distinct titanomagnetite (Tmt) populations formed: (1) skeletal crystals, isolated or partially embedded in clinopyroxene (Cpx); (2) anhedral crystals, always attached to Cpx; (3) flattened needle-shaped crystals, embedded in Cpx. These morphologically different Tmt populations formed in response to one cooling event, with varying nucleation mechanisms and at different undercooling conditions. The clustered three-dimensional distribution of population 2 and 3 Tmt grains and the high proportion of Tmt-Cpx interfaces sharing CORs indicate that these Tmt grains heterogeneously nucleated on Cpx. The near-random three-dimensional distribution of (often isolated) population 1 Tmt grains, together with the low proportion of Tmt-Cpx interfaces sharing CORs, imply their isolated, possibly homogeneous nucleation, potentially followed by heterogeneous nucleation of Cpx on population 1 Tmt. Heterogeneous nucleation in slightly to moderately undercooled magmas should affect the sequence of crystallization as well as morphology and clustering of crystals, which may actively contribute to the variation of rheological parameters like viscosity. Finally, observed intra- and inter-sample variations in Tmt-Cpx COR frequencies indicate the potential for this parameter to record further petrological information.

Effect of undercooling on clinopyroxene crystallization in a high K basalt: Implications for magma dynamics at Stromboli volcano - F. Colle; M. Masotta; S. Costa; S. Mollo; P. Landi; A. Pontesilli; S. Peres; L. Mancini (Lithos, 2023)

PFAS levels and exposure determinants in sensitive population groups - L. Fábelová; A. Beneito; M. Casas; A. Colles; L. Dalsager; E. Den Hond; C. Dereumeaux; K. Ferguson; L. Gilles; E. Govarts; A. Irizar; M.J. Lopez Espinosa; et al. (Chemosphere, 2023)

Approaches to mixture risk assessment of PFASs in the European population based on human hazard and biomonitoring data - W. Bil; E. Govarts; M.J. Zeilmaker; M. Woutersen; J. Bessems; Y. Ma; C. Thomsen; L.S. Haug; S. Lignell; I. Gyllenhammar; L. Palkovicova Murinova; L. Fabelova; et al. (International Journal of Hygiene and Environmental Health, 2023)

PFAS levels and determinants of variability in exposure in European teenagers – Results from the HBM4EU aligned studies (2014–2021) - D. Richterová; E. Govarts; L. Fábelová; K. Rausová; L. Rodriguez Martin; L. Gilles; S. Remy; A. Colles; L. Rambaud; M. Riou; C. Gabriel; D. Sarigiannis; et al. (International Journal of Hygiene and Environmental Health, 2023)

Probucol Protects Neuronal Cells Against Peroxide-Induced Damage and Directly Activates Glutathione Peroxidase-1 - Danúbia B. Santos; Dirleise Colle; Eduardo L. G. Moreira; Alessandra A. Santos; Mariana A. Hort; Karin Santos; Jean P. Oses; Guilherme Razzera; Marcelo Farina (Molecular Neurobiology, 2020)

Ectoparasites of small mammals in a fragmented area of the southern Amazonia: interaction networks and correlations with seasonality and host sex - Ravena F. B. de Mendonça; Ana C. Colle; Leodil C. Freitas; Thiago F. Martins; Maurício C. Horta; Glauber M. B. Oliveira; Richard C. Pacheco; Lúcia A. F. Mateus; Rogério V. Rossi (Experimental and Applied Acarology, 2020)

The Future of Midlatitude Cyclones - Jennifer L. Catto; Duncan Ackerley; James F. Booth; Adrian J. Champion; Brian A. Colle; Stephan Pfahl; Joaquim G. Pinto; Julian F. Quinting; Christian Seiler (Current Climate Change Reports, 2019)
Purpose of Review This review brings together recent research on the structure, characteristics, dynamics, and impacts of extratropical cyclones in the future. It draws on research using idealized models and complex climate simulations, to evaluate what is known and unknown about these future changes. Recent Findings There are interacting processes that contribute to the uncertainties in future extratropical cyclone changes, e.g., changes in the horizontal and vertical structure of the atmosphere and increasing moisture content due to rising temperatures. Summary While precipitation intensity will most likely increase, along with associated increased latent heating, it is unclear to what extent and for which particular climate conditions this will feedback to increase the intensity of the cyclones. Future research could focus on bridging the gap between idealized models and complex climate models, as well as better understanding of the regional impacts of future changes in extratropical cyclones.

Storm surge return levels induced by mid-to-late-twenty-first-century extratropical cyclones in the Northeastern United States - Ning Lin; Reza Marsooli; Brian A. Colle (Climatic Change, 2019)

Incorporating inland flooding into hurricane evacuation decision support modeling - Kun Yang; Rachel A. Davidson; Humberto Vergara; Randall L. Kolar; Kendra M. Dresback; Brian A. Colle; Brian Blanton; Tricia Wachtendorf; Jennifer Trivedi; Linda K. Nozick (Natural Hazards, 2019)

Genome‐wide association of functional traits linked with C ampylobacter jejuni survival from farm to fork - Koji Yahara; Guillaume Méric; Aidan J. Taylor; Stefan P. W. de Vries; Susan Murray; Ben Pascoe; Leonardos Mageiros; Alicia Torralbo; Ana Vidal; Anne Ridley; Sho Komukai; Helen Wimalarathna; et al. (Environmental Microbiology, 2017)
Summary Campylobacter jejuni is a major cause of bacterial gastroenteritis worldwide, primarily associated with the consumption of contaminated poultry. C. jejuni lineages vary in host range and prevalence in human infection, suggesting differences in survival throughout the poultry processing chain. From 7343 MLST‐characterised isolates, we sequenced 600 C. jejuni and C. coli isolates from various stages of poultry processing and clinical cases. A genome‐wide association study (GWAS) in C. jejuni ST‐21 and ST‐45 complexes identified genetic elements over‐represented in clinical isolates that increased in frequency throughout the poultry processing chain. Disease‐associated SNPs were distinct in these complexes, sometimes organised in haplotype blocks. The function of genes containing associated elements was investigated, demonstrating roles for cj1377c in formate metabolism, nuoK in aerobic survival and oxidative respiration, and cj1368‐70 in nucleotide salvage. This work demonstrates the utility of GWAS for investigating transmission in natural zoonotic pathogen populations and provides evidence that major C. jejuni lineages have distinct genotypes associated with survival, within the host specific niche, from farm to fork.

Natural killer cells in acute myeloid leukemia patients: from phenotype to transcriptomic analysis - G. Venton; Y. Labiad; J. Colle; A. Fino; S. Afridi; M. Torres; S. Monteuil; B. Loriod; N. Fernandez-Nunez; L. Farnault; P. Suchon; J. C. Mattei; et al. (Immunologic Research, 2016)

Evidence for Directional Wind Response in Controlling Inter-annual Variations in Duration and Areal Extent of Summertime Hypoxia in Western Long Island Sound - Robert E. Wilson; Sean D. Bratton; Jindong Wang; Brian A. Colle (Estuaries and Coasts, 2015)

A Review of Historical and Future Changes of Extratropical Cyclones and Associated Impacts Along the US East Coast - Brian A. Colle; James F. Booth; Edmund K. M. Chang (Current Climate Change Reports, 2015)

Cryptic ecology among host generalist Campylobacter jejuni in domestic animals - Samuel K. Sheppard; Lu Cheng; Guillaume Méric; Caroline P. A. de Haan; Ann‐Katrin Llarena; Pekka Marttinen; Ana Vidal; Anne Ridley; Felicity Clifton‐Hadley; Thomas R. Connor; Norval J. C. Strachan; Ken Forbes; et al. (Molecular Ecology, 2014)
Homologous recombination between bacterial strains is theoretically capable of preventing the separation of daughter clusters, and producing cohesive clouds of genotypes in sequence space. However, numerous barriers to recombination are known. Barriers may be essential such as adaptive incompatibility, or ecological, which is associated with the opportunities for recombination in the natural habitat. Campylobacter jejuni is a gut colonizer of numerous animal species and a major human enteric pathogen. We demonstrate that the two major generalist lineages of C. jejuni do not show evidence of recombination with each other in nature, despite having a high degree of host niche overlap and recombining extensively with specialist lineages. However, transformation experiments show that the generalist lineages readily recombine with one another in vitro. This suggests ecological rather than essential barriers to recombination, caused by a cryptic niche structure within the hosts.

Modified plant architecture to enhance crop disease control: genetic control and possible value of upright fruit position in cucumber - Rebecca Grumet; Marivi Colle; Kaori Ando; Da-Sen Xie; Laura Havenga; Jessica A. Switzenberg (European Journal of Plant Pathology, 2013)

Progressive genome‐wide introgression in agricultural Campylobacter coli - Samuel K. Sheppard; Xavier Didelot; Keith A. Jolley; Aaron E. Darling; Ben Pascoe; Guillaume Meric; David J. Kelly; Alison Cody; Frances M. Colles; Norval J. C. Strachan; Iain D. Ogden; Ken Forbes; et al. (Molecular Ecology, 2013)
Hybridization between distantly related organisms can facilitate rapid adaptation to novel environments, but is potentially constrained by epistatic fitness interactions among cell components. The zoonotic pathogens C ampylobacter coli and C . jejuni differ from each other by around 15% at the nucleotide level, corresponding to an average of nearly 40 amino acids per protein‐coding gene. Using whole genome sequencing, we show that a single C. coli lineage, which has successfully colonized an agricultural niche, has been progressively accumulating C. jejuni DNA . Members of this lineage belong to two groups, the ST ‐828 and ST ‐1150 clonal complexes. The ST ‐1150 complex is less frequently isolated and has undergone a substantially greater amount of introgression leading to replacement of up to 23% of the C. coli core genome as well as import of novel DNA . By contrast, the more commonly isolated ST ‐828 complex bacteria have 10–11% introgressed DNA , and C. jejuni and nonagricultural C. coli lineages each have C. coli that colonize agriculture, and consequently cause most human disease, have hybrid origin, but this cross‐species exchange has so far not had a substantial impact on the gene pools of either C. jejuni or nonagricultural C. coli . These findings also indicate remarkable interchangeability of basic cellular machinery after a prolonged period of independent evolution.

Specialists leave fewer descendants within a region than generalists - Wim A. Ozinga; Audrey Colles; Igor V. Bartish; Françoise Hennion; Stephan M. Hennekens; Sandrine Pavoine; Peter Poschlod; Marie Hermant; Joop H. J. Schaminée; Andreas Prinzing (Global Ecology and Biogeography, 2013)
Aim Current conservation biology suggests that across ecological time‐scales specialist species existing in the recent past have left on average fewer descendant populations today than generalist species. Conversely, the speciation literature suggests that on an evolutionary time‐scale specialists leave as many or more descendant lineages as generalists, i.e. they have high rates of global diversification. This begs the question: which of these two processes has more influence on the regional scale, i.e. do specialists leave more or fewer descendants than generalists within a region? Location The flora of the N etherlands. Methods We quantified niche volume of 707 plant species from coexistence data and ecological indicator values and used sister taxon comparisons to compare specialist and generalist sister taxa for the relative numbers of descendants across three temporal scales: ecological, microevolutionary and macroevolutionary. Results We show, first, that specialist species are more likely to be currently declining, i.e. to leave only few descendant populations. Second, specialists are less likely to be currently diversifying into intra‐specific taxa. Finally, most specialist clades left fewer descendant species within a region than their generalist sister clades. These results were consistent across sublineages, unbiased by geographic sampling of lineages and environments, and held after accounting for species life histories. Differences between specialist and generalist sister clades increased with clade age, suggesting that they reflect differences in rates at which specialists left descendants (rather than differences in ecological limits to the numbers of specialists and generalists). Main conclusions Specialists left only few descendants within a region (i.e. the N etherlands), both at ecological, microevolutionary and macroevolutionary scales. While specialists may leave numerous evolutionary descendants at a global scale, these might be absent from most regions. Humans, by threatening specialist species, may hence further accelerate biotic homogenization with descendants of generalist lineages proliferating within regions while specialist lineages disappear.

Exposure to Traffic-Related Air Pollutants in the Perinatal Period of Life in Relation to Respiratory Health in Infancy - G. Koppen; K. Bloemen; A. Colles; V. Nelen; K. Desager; G. Schoeters (Critical Reviews in Environmental Science and Technology, 2011)

Dynamics of Campylobacter colonization of a natural host, Sturnus vulgaris (European Starling) - F. M. Colles; N. D. McCarthy; J. C. Howe; C. L. Devereux; A. G. Gosler; M. C. J. Maiden (Environmental Microbiology, 2009)
Summary Wild European Starlings ( Sturnus vulgaris ) shed Campylobacter at high rates, suggesting that they may be a source of human and farm animal infection. A survey of Campylobacter shedding of 957 wild starlings was undertaken by culture of faecal specimens and genetic analysis of the campylobacters isolated: shedding rates were 30.6% for Campylobacter jejuni , 0.6% for C. coli and 6.3% for C. lari. Genotyping by multilocus sequence typing (MLST) and antigen sequence typing established that these bacteria were distinct from poultry or human disease isolates with the ST‐177 and ST‐682 clonal complexes possibly representing starling‐adapted genotypes. There was seasonal variation in both shedding rate and genotypic diversity, both exhibiting a maximum during the late spring/early summer. Host age also affected Campylobacter shedding, which was higher in younger birds, and turnover was rapid with no evidence of cross‐immunity among Campylobacter species or genotypes. In nestlings, C. jejuni shedding was evident from 9 days of age but siblings were not readily co‐infected. The dynamics of Campylobacter infection of starlings differed from that observed in commercial poultry and consequently there was no evidence that wild starlings represent a major source of Campylobacter infections of food animals or humans.

Campylobacter infection of broiler chickens in a free‐range environment - Frances M. Colles; Tracey A. Jones; Noel D. McCarthy; Samuel K. Sheppard; Alison J. Cody; Kate E. Dingle; Marian S. Dawkins; Martin C. J. Maiden (Environmental Microbiology, 2008)
Summary Campylobacter jejuni is the most common cause of bacterial gastroenteritis worldwide, with contaminated chicken meat considered to represent a major source of human infection. Biosecurity measures can reduce C. jejuni shedding rates of housed chickens, but the increasing popularity of free‐range and organic meat raises the question of whether the welfare benefits of extensive production are compatible with food safety. The widespread assumption that the free‐range environment contaminates extensively reared chickens has not been rigorously tested. A year‐long survey of 64 free‐range broiler flocks reared on two sites in Oxfordshire, UK, combining high‐resolution genotyping with behavioural and environmental observations revealed: (i) no evidence of colonization of succeeding flocks by the C. jejuni genotypes shed by preceding flocks, (ii) a high degree of similarity between C. jejuni genotypes from both farm sites, (iii) no association of ranging behaviour with likelihood of Campylobacter shedding, and (iv) higher genetic differentiation between C. jejuni populations from chickens and wild birds on the same farm than between the chicken samples, human disease isolates from the same region and national samples of C. jejuni from chicken meat.